Հայոց Արևելից կողմանց վարչաքաղաքական կացությունը 5-13-րդ դարերում (համառոտ ակնարկ)/ADMINISTRATIVE AND POLITICAL SITUATION OF THE ARMENIAN EASTERN REGIONS IN THE 5th-13th CENTURIES (BRIEF ESSAY) - HOVSEPYAN, VOLODYA (Scientific Artsakh, 2025)
The purpose of this article is to demonstrate that studying the medieval administrative and political landscape of the eastern provinces of Greater Armenia holds not only scholarly but also political importance. This is particularly relevant given that Azerbaijani historiography, driven by political motives, distorts the history of the Armenian people and even questions the existence of Armenian statehood. This occurs against the backdrop of contemporary Azerbaijani leadership openly laying claims not only to Artsakh but also to the territory of the Republic of Armenia. The objectives of the research are: 1. to interpret the issues related to the abolition of the kingdom of Aghvan, the establishment of the marzpanate and the time of accession of the provinces of Artsakh and Utik, which separated from Armenia, to Aghvan using new substantiations. 2. to determine the administrative and political status of the eastern provinces of Armenia within the Aghvan province. 3. to present the situation of the local Armenian princely houses after the abolition of the marzpanate of Aghvan in the IX-XIII centuries. In the course of the work we applied a number of special methods, namely: structural, historical-legal, systematic, analytical, etc. We have substantiated that after the abolition of the marzpanate of Aghvan in the IX-XIII cc. In this paper, we have demonstrated that following the dissolution of the Kingdom of Greater Armenia, its eastern provinces—Artsakh and Utik—though incorporated into the administrative-political unit of Caucasian Albania, remained ethnically and culturally Armenian. This continuity laid the foundation for the subsequent development of Armenian statehood in various forms, including the Eastern Kingdom of Hamam, the Principalities of Parisos and Khachen, the Melikdoms of Khams, the Nagorno-Karabakh Autonomous Oblast, and the Nagorno-Karabakh (Artsakh) Republic from 1991 to 2023.